Stakeholder Theory As an Ethical Approach to Effective Management: applying the theory to multiple contexts - S. Harrison, Jeffrey; Freeman, R. Edward; Cavalcanti Sá de Abreu, Mônica (Review of Business Management, 2015)
Objective – This article provides a brief overview of stakeholder theory, clears up some widely held misconceptions, explains the importance of examining stakeholder theory from a variety of international perspectives and how this type of research will advance management theory, and introduces the other articles in the special issue. Design/methodology/approach – Some of the foundational ideas of stakeholder theory are discussed, leading to arguments about the importance of the theory to management research, especially in an international context. Findings – Stakeholder theory is found to be a particularly useful perspective for addressing some of the important issues in business from an international perspective. It offers an opportunity to reinterpret a variety of concepts, models and phenomena across may different disciplines. Practical implications – The concepts explored in this article may be applied in many contexts, domestically and internationally, and across business disciplines as diverse as economics, public administration, finance, philosophy, marketing, law, and management. Originality/value – Research on stakeholder theory in an international context is both lacking and sorely needed. This article and the others in this special issue aim to help fill that void.